Design of a Safety Device Ultra Violet Light for Mercury Identification in Whitening Cream with Thin Layer Chromatography Method Using Camera OV7670 Based on Arduino Uno - Hasmah Hasmah; Risnawaty Alyah; Usman Umar (Jurnal Teknokes, 2022)
Mercury is also called “air raksa” or hydrargyrum which is a chemical element with the symbol Hg and belongs to the heavy metal group with a liquid form and silvery color. Mercury is a heavy metal that is harmful to the skin when added to cosmetics, especially creams on the face, even in small concentrations because it is toxic. Identification of Mercury in the laboratory using the thin layer chromatography method with the help of ultra violet light causes medical personnel to be vulnerable to exposure to ultra violet rays which have a negative impact on eye and skin health. The purpose of this research is to design a safety to minimize exposure to ultra violet rays when identify mercury. OV76070 which can reduce direct contact with ultra violet light identifies the present of Mercury in the whitening cream will be carried out using a thin layer chromatography separation method with the help ultra violet 254nm-366nm. With the help of ultra violet lamps 254nm-366nm, and it is hoped that Mercury inspection using the OV7670 camera will be more efficient and accurate. The tool used in this research is the OV7670 camera with a power of 640 – 460 pixels (VGA) to take photo on thin layer chromatography plate, ultra violet lamps 254nm- 366nm. Overall the design of this tool is controlled by the Arduino Uno microcontroller. Image from the OV7670 camera can be monitored at the Liquid Crystal Display in the form of the appearance fluorescence spot indicating the presence of Mercury in the whitening cream sample.